Effects of metal modification on titanium dioxide for photocatalytic reduction of carbon dioxide - Liu, Dong (2012)
To study the effects of metal modification on titanium dioxide (TiO2) for photocatalytic reduction of carbon dioxide (CO2), a series of pure and metal modified TiO2 catalysts (referred as SG TiO2 and M/TiO2, respectively) were synthesized via a refined sol-gel process. The metals chosen to modify TiO2 included Cu, Zn, and Rh. These catalysts were then characterized by using various analytical techniques, including ICP-MS, powder XRD, XPS, TEM, N2 adsorption isotherms, Cu surface area and dispersion measurement, and DR UV-Vis. It was found that all the sol-gel derived TiO2 catalysts had the same crystalline phase of anatase, and similar particle sizes (11-16 nm) and surface areas (50.24-63.37 m2/g). It is worthy to note that, even though synthesized via the same sol-gel process, the three added metals modified their TiO2 supports differently. The added Cu and Zn were loaded on the surface ofTiO2 with their chemical states to be CU2O and ZnO, respectively. Whereas, the added Rh was substitutionally doped into the lattice of its TiO2 supports. The specific surface area and dispersion of the added Cu on the surface of CulTiO2 were further measured by using N2O as adsorbate. It was found that the aggregation of the added Cu occurred when the Cu ratio of Cu/TiO2 over-increased (over 0.03 wt%). The following CO2 photoreduction experiments confirmed that the added Cu and Rh were able to significantly improve the activity of TiO2 for CO2 photoreduction to methane, wherein the activities of the best performing 0.03 wt% Cu/TiO2 and 0.01 wt% Rh/TiO2 were around 10-times higher than that of SG/TiO2. The added Cu and Rh were expected to affect the activity of TiO2 via different ways. The combination of the loaded Cu and TiO2 was considered to be a composite semiconductor catalyst, and the Cu dispersion dominated the activity of Cu/TiO2. In comparison, the doped Rh was able to affect the activity of TiO2 by introducing an additional energy level to the band-gap of TiO2. Finally, TiO2 catalysts simultaneously loaded by Cu and doped by Rh (Rh/Cu/TiO2, synthesized via the identical sol-gel process) were also tested for CO2 photoreduction. The results indicate that the loaded Cu and doped Rh were able to synergistically enhance the activity of TiO2 for CO2 photoreduction, allowing the optimal Rh/Cu/TiO2 (0.06 wt% Rh/O.03 wt% Cu/TiO2) to present even better (at least 25 % higher) activity than any of the Cu/TiO2 or Rh/TiO2 in this work.